Direct Production of a Novel Iron-Based Nanocomposite from the Laser Pyrolysis of Fe(CO)5/MMA Mixtures: Structural and Sensing Properties. (21st March 2010) - Alexandrescu, R.; Morjan, I.; Tomescu, A.; Simion, C. E.; Scarisoreanu, M.; Birjega, R.; Fleaca, C.; Gavrila, L.; Soare, I.; Dumitrache, F.; Prodan, G.
Abstract : Iron/iron oxide-based nanocomposites were prepared by IR laser sensitized pyrolysis of Fe ( CO ) 5 and methyl methacrylate (MMA) mixtures. The morphology of nanopowder analyzed by TEM indicated that mainly core-shell structures were obtained. X-ray diffraction techniques evidence the cores as formed mainly by iron/iron oxide crystalline phases. A partially degraded (carbonized) polymeric matrix is suggested for the coverage of the metallic particles. The nanocomposite structure at the variation of the laser density and of the MMA flow was studied. The new materials prepared as thick films were tested for their potential for acting as gas sensors. The temporal variation of the electrical resistance in presence of NO 2, CO, and CO 2, in dry and humid air was recorded. Preliminary results show that the samples obtained at higher laser power density exhibit rather high sensitivity towards NO 2 detection and NO 2 selectivity relatively to CO and CO 2 . An optimum working temperature of 200 ° C was found.